EARLY DETECTION OF MENTAL EMOTIONAL DISORDERS (DEPRESSION, ANXIETY, AND STRESS) IN PATIENTS WITH DIABETES MELLITUS - Giyaningtyas, Ika Juita; Elizabeth, Beatrix; Sartika, Aprilina (LPPM Univ. Ibn Khaldun Bogor, 2024)
Chronic diseases such as diabetes mellitus can affect the psychological state of the patient. Negative emotional responses to the diagnosis that one has the disease can include denial or unwillingness to acknowledge reality, anxiety, anger, guilt, and depression. These conditions are mental emotional disorders that often occur in patients with chronic diseases. Diabetes mellitus patients who come to the doctor or to other health services are not known to have mental emotional disorders, so they do not get further treatment. This will certainly have an impact on the failure of monitoring therapy which further affects the prognosis. Based on the analysis of the situation and existing problems, it is necessary to conduct early detection related to mental emotional disorders or psychosocial mental health problems that accompany diabetes mellitus patients in the Cibarusah Health Center area. Early detection is carried out with the Self Reporting Quetionnaire 20 (SRQ-20) instrument. Based on the results of early detection that has been carried out, it is concluded that the majority of patients with diabetes mellitus experience mental emotional disorders, as many as 56%. Patients must realize the importance of early detection and actively participate in treatment. Prevention efforts are important by involving diabetes management, promotion of a healthy lifestyle, social support, and constant monitoring of changes in mental symptoms.